Preliminary foliar anatomical assessment of four Vanilla species (Orchidaceae) from Perak, Malaysia - Mohd Raffi, Mohd Akmal; Abdullah, Nur Ashikin Psyquay; Mohd Yunus, Noor Syaheera; Go, Rusea (Universiti Putra Malaysia Press, 2019)
Assessment of the leaf anatomy among Vanilla griffithii, Vanilla kinabaluensis, Vanilla sanguineovenosa and Vanilla sp. 1 from Perak showed generic characterization of the epidermal layer and leaf lamina, suggesting the genus to possess plesiomorphic characters from its progenitor except for the leaf margin outlines. The species were found to differ interspecifically and acknowledged to possess taxonomic value. Leaf margin among the species showed similarity in tapering outline but distinguished in the overall shape and apical curve.